Eagle syndrome: a case report - Henrique Beletáble Fonseca; Sérgio Moreira da Costa; Liliane Carvalho Jamil (Revista Brasileira de Cirurgia Plástica, 2019)
Eagle syndrome is a rare condition, and its etiology has not yet been well established and its correct treatment is uncertain. Its treatment must be defined together with the patient, be it conservative or surgical, always taking into consideration the patient's expectations, in addition to a solid professional expertise in the modality chosen for the treatment. In this article, we present the case of a 35-year-old patient who was admitted to the Felício Rocho Hospital and discuss the various aspects of the disease, including the treatment modality chosen for the case.